Predicting admission to long‐term care and mortality among community‐based, dependent older people in Ireland. (17th April 2019) - Aspell, Niamh; O'Sullivan, Maria; O'Shea, Eamon; Irving, Kate; Duffy, Chloe; Gorman, Rebecca; Warters, Austin
Abstract : Objective: To identify factors that predict admission to long‐term care (LTC) and mortality among community‐based, dependent older people in Ireland, who were in receipt of formal home support. Methods: An audit was conducted of all community‐dwelling older adults receiving government funded home support during 2017 in the Dublin North Central, Health Service Executive administrative area. Data were extracted from the Common Summary Assessment Report (CSAR), a mandatory form used in the provision of home support. Multiple logistic regression analysis was used to examine the factors associated with admission to LTC and mortality, with the results presented as odds ratios (OR) and 95% confidence intervals. Results: The audit comprised 1597 community‐dwelling older adults with a mean age of 83.3 (SD: 7.2) years. The prevalence of transition to LTC and mortality was 8% and 9%, respectively, during the 12‐month period. Factors significantly associated with admission to LTC were "cognitive dysfunction" [OR 2.10 (1.41‐3.14), P  < .001] and the intensity of home support [OR 1.05 (1.01‐1.06), P  < .003], as measured by weekly formal care hours. Physical dependency and advanced age (aged 95 years +) were significantly associated with mortality in this population ( P  < .001). Conclusion: "Cognitive dysfunction" and intensity of formal home support were associated with transition to LTC, while physical dependency and advanced age were associated with mortality. Investment in personalised, cognitive‐specific, services and supports are necessary to keep people with dementia and related cognitive impairments living at home for longer.